SPECIATION, MOBILITY AND POTENTIAL TOXICITY OF METALS (CR, CO, CU AND MN) IN SOIL SAMPLES FROM DUMPSITES IN KANO METROPOLIS - Alhaji Adamu, Yahaya; Olaleye, A. A. (FUDMA JOURNAL OF SCIENCES, 2022)
Soil pollution by heavy metals is a global environmental problem. The need to keep the environment clean is increasingly becoming a global concern. Heavy metals are one group of pollutants that are widespread in our environment. They tend to persist indefinitely once they enter the soil. Their mobility and toxicity depend on their forms and oxidation states in the soil. This research presents the speciation, mobility and potential toxicity of Cr, Co, Cu and Mn in soils from some dumpsites in Kano, using a six-step sequential extraction method and AAS analysis. The results revealed the pH of the soils to range from 6.20-7.80. Percentage composition of clay and organic matter ranged from 6.00-16.58 % and 0.48- 4.30 % respectively. The results showed that the metals are bioavailable at different forms evident from their distribution pattern in the different fractions and therefore the soils should not be used for cultivation to avoid the metals getting into the food chain. The mobility factor values ranging between 14.38 % and 61.48 % for dry season; 15.63 % and 74.74 % for rainy season showed the metals to be very mobile especially Co, Cu, and Mn. This could lead to potential pollution of the agricultural produce and ground water in this area and hence have toxic effects on human lives. This result can serve as a guide to researchers on the appropriate method to reclaim the soils in this area based on the pattern of distribution of the metals in different geochemical phases.